The Elements and Practice of Rigging, Seamanship, and Naval Tactics. Volume 2, The Art of Sail-Making - Steel, David (Place of publication not identified : publisher not identified, 1809)
David Steel was one of the most respected and prolific naval publishers of the late eighteenth and early nineteenth centuries. His publications focused on naval strategy and shipbuilding techniques. This influential four-volume work, first published in 1794, was the first comprehensive English manual of best naval practice. Designed for aspiring young officers, it established Steel's reputation as a publisher. The book describes theoretical and practical aspects of masts, rigging, and sails, and the science of sailing. The combination of practical advice supported by scientific and mathematical explanations and numerous illustrations provides valuable insights into British seamanship during the Napoleonic wars. Volume 2, reissued here in the 1809 edition, describes the art of sailmaking, the technical terms relating to it, the tools required, the quality of canvas used for different sails in naval and merchant vessels, and how to calculate the quantities needed.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).